Enhanching Student Character Based on Conservation Values (Case Study at Semarang State University) - Masruki Masruki (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Conservation university that has to be the characteristic of Semarang State University, has a strategic meaning in the context of character development. This is related to the meaning of conservation it self,  not only a physical connotation, but it also cultural and values. Conservation values manifested in daily life interactions, based on three important pillars,such as the protection, preservation, and sustainable use. Values and culture which framed by the pillars will emit value of life which could be the basis of character development.Therefore, through this formula will be embedded in the students, the character  which can contribute to the life of the nation. Keywords: Character, Conservation, Value